World records: How much athlete? How much technology? - de Koning, J. J. (International Journal of Sports Physiology and Performance, 2010)
The quality of performance during international competitions such as the Olympic Games and various world championships is often judged by the number of world records attained. The simple fact that world records continue to improve is evidence that sports performance is progressing. Does this also mean that athletes are improving? Is the continual progression of world-record performances evidence that contemporary athletes are superior to the athletes who performed in the past? Technological developments may obscure insight into the athletic enhancement made by athletes over the years. This commentary tries to separate technological and athletic enhancement in the progression of world records by the use of a power balance model.